Machinery component maintenance and repair - Bloch, Heinz P., 1933- (Bloch, Heinz P., 1933- Practical machinery management for process plants., 2005)
The names Bloch and Geitner are synonymous with machinery maintenance and reliability for process plants. They save companies like Dow and Equilon millions of dollars a year by extending the life of rotating machinery in their plants. Extending the life of existing machinery is the name of the game in the process industries, not designing new machinery. This series by Bloch and Geitner was the first and is still the best, most comprehensive source for doing just that. This classic text on reliability has been revised to include all new material on risk management, pre-grouted bases, laser alignment, cartridge seals maintenance, and many other topics which have undergone many developments since the last revision. *Helps engineers save their companies hundreds of thousands of dollars a year by reducing machinery downtime *Now in its third edition, with a twenty-year history of success *Details the money-saving techniques used by many of the world's leading companies, including Exxon, DuPont, Dow, and dozens of others.